Ruth Mack Brunswick papers - Brunswick, Ruth Mack.; Pankejeff, Sergius, 1887-1979.
Correspondence, writings, patient files, notes, and other papers chiefly concerning Brunswick's theories of a developmental phase preceding the Oedipus complex and her analysis of Sergius Pankejeff, a former patient of Sigmund Freud referred to as the "Wolf Man" in Freud's case study. Includes notes, writings, and a record of dreams by Pankejeff. Correspondents include Anna Freud, Martha Freud, and other members of the Freud family; Ives Hendrick; and Pankejeff.
Psychoanalyst. Born 1897; died 1946.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Keywords: Freud, Anna, -- 1895-1982 -- Correspondence; Freud, Martha, -- 1861-1951 -- Correspondence; Hendrick, Ives, -- 1898-1972 -- Correspondence; Pankejeff, Sergius, -- 1887-1979.; Pankejeff, Sergius, -- 1887-1979 -- Correspondence; Freud family -- Correspondence; Dreams; Oedipus complex; Psychoanalysis